Effects of YSZ powder properties on its corrosion behaviour for solid oxide membrane (SOM) electrolysis process. Issue 15 (December 2019) - Hwang, Kuk-Jin; Shin, Miyoung; Lee, Young Wook; Lee, Myung-Hyun; Lee, Heesoo; Shin, Tae Ho
Abstract: The solid oxide membrane (SOM) process is an environmentally friendly and innovative technology that can produce valuable metals directly from their oxides. In the SOM process, a yttria-stabilized zirconia (YSZ) tube is normally immersed the molten salt containing dissolved metal oxides and oxygen anions that move to the SOM tube where they are reduced without any emission. However, the YSZ phase transition and yttrium dissolution by the reaction with the flux reduce the SOM stability and lifetime. Here, we investigated the effect of powder characteristics on YSZ stability in the SOM electrolysis environment. Thus, powder with good formability such as high flowability and tap/untap density showed a 2% decrease in electrical conductivity, but a 17% decrease in low formability powders. The cause of the degradation is the penetration of salt ions into the lattice and the elution of yttrium ions, which results in a phase transition.